2020
DOI: 10.1038/s41598-020-73820-8
|View full text |Cite
|
Sign up to set email alerts
|

Hot spot profiles of SARS-CoV-2 and human ACE2 receptor protein protein interaction obtained by density functional tight binding fragment molecular orbital method

Abstract: The prevalence of a novel β-coronavirus (SARS-CoV-2) was declared as a public health emergency of international concern on 30 January 2020 and a global pandemic on 11 March 2020 by WHO. The spike glycoprotein of SARS-CoV-2 is regarded as a key target for the development of vaccines and therapeutic antibodies. In order to develop anti-viral therapeutics for SARS-CoV-2, it is crucial to find amino acid pairs that strongly attract each other at the interface of the spike glycoprotein and the human angiotensin-con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 32 publications
7
34
0
Order By: Relevance
“…The fragment molecular orbital method was developed by Kitaura et al in 1999 [34]. In recent years, FMO has been increasingly used in new drug designs based on accurate energy calculations, especially in protein-ligand and protein-protein interaction analysis [35][36][37][38][39][40][41]. In order to investigate PPI, a 3-dimensional scattered pair interaction energy (FMO/3D-SPIE) analysis was introduced to sort vital interactions with the FMO method, and it efficiently correlated the results with experimental site-directed mutagenesis results [36].…”
Section: Introductionmentioning
confidence: 99%
“…The fragment molecular orbital method was developed by Kitaura et al in 1999 [34]. In recent years, FMO has been increasingly used in new drug designs based on accurate energy calculations, especially in protein-ligand and protein-protein interaction analysis [35][36][37][38][39][40][41]. In order to investigate PPI, a 3-dimensional scattered pair interaction energy (FMO/3D-SPIE) analysis was introduced to sort vital interactions with the FMO method, and it efficiently correlated the results with experimental site-directed mutagenesis results [36].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the essential hot spots of the 15 common amino acid residues on ACE2 and the 28 common residues on SARS S-proteins identified in the current study are partially in agreement with hot spots on ACE2 identified by Lim et al via FMO calculations using the self-consistent charge density-functional tightbinding method with third-order expansion using semiempirical dispersion (DFTB3/D) method. 13 Lim et al showed two sizable hot spot regions, where several hot spots were assembled 13 . Their results were almost consistent with our results, showing that the common hot spots between ACE2 and S-protein were as follows: The first hot spot region included Q24ACE2, A25ACE2, F28ACE2, D30ACE2, K31ACE2, E35ACE2, and Y83ACE2, which interacted with K417Spike, L455Spike, S477Spike, E484Spike, F486Spike, N487Spike, Y489Spike, and Q493Spike in the SARS-CoV-2.…”
Section: Hot Spot Analysis Of S-proteinmentioning
confidence: 99%
“…Lim et al has shown two large hot spot regions from FMO-based interaction analysis of ACE2 and S-proteins of the SARS-CoV-2. 13 Since the hot spots of S-protein with the several neutralizing antibodies of the SARS-CoV coincided with the 2 nd hot spot region, the authors speculated that the 2 nd hot spot region was crucial for drug design against the SARS-CoV-2. However, our results suggest that all key hot spots for molecular recognition between the SARS-CoV-2 S protein and ACE2 may play a significant role in the design of neutralizing antibodies.…”
Section: Fmo-based Epitope Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… 17 , 18 As for QM calculation, the fragment molecular orbital (FMO) method 19 , 20 is one of the methods that can treat the entire protein with uniform accuracy. The FMO calculation for several specific SARS-CoV-2-related proteins, such as the S protein, 21 25 Mpro, 26 30 and RdRp, 31 have been performed using the ABINIT-MP program 32 , 33 and the GAMESS program. 34 36 The ABINIT-MP program used in this paper is capable of performing precise electron correlation calculations at the MP4 (SDQ) level for S proteins of up to 3300 residues using the Fugaku supercomputer.…”
Section: Introductionmentioning
confidence: 99%